Effect of relining and microwave disinfection on the dimensional stability of denture bases - Carvalho, Paula Carolina Komori de; Costa, Fernanda Calvo; Bourg, Natassia Bricks; Borges, Alexandre Luiz Souto; Paes Junior, Tarcisio José de Arruda (Brazilian Dental Science, 2025)
Objective: To evaluate the effect of microwave disinfection on dimensional stability of acrylic resin denture base and relined. Material and Methods: 24 maxillary complete dentures were assigned to 2 groups; GA - acrylic base (Power microwave, Vipi-Wave) and GR - relined (New Truliner). For all prosthesis the thickness of the base, reliner and tooth position were completely standardized. The intact and relined denture bases were divided into 3 groups and evaluated after: polymerization (C - control group); microwave disinfection (D); microwave disinfection + water storage for 14 days (D14). Microwave disinfection was performed for 3 min at 650W. The alteration of tooth position of each group was measured comparing the images imported to Image Tool software. The linear distance between different points marked on each side of the arch (canine, molar and incisor) made before polymerization served as baseline and after. Differences between the baseline and those subsequently were used to calculate the percent of dimensional changes. Results: The relined dentures without disinfection (GR-C) showed an average increase in tooth position distances of approximately 10.4% (± 5.2%), indicating dimensional expansion. Immediate microwave disinfection caused a significant decrease in distances in both acrylic base (GA-D: 8.9% reduction ± 3.7%) and relined groups (GR-D: 6.6% reduction ± 3.5%), reflecting material contraction. After disinfection plus 14 days water storage (D14), dimensional changes were minimal, close to control values (GA-D14: 1.7% decrease ± 2.1%; GR-D14: 0.9% decrease ± 1.7%). Conclusion: The microwave disinfection influenced tooth position regardless of relining. KEYWORDS Acrylic resin; Complete denture; Dental prosthesis; Disinfection; Microwave.